Healing Evaluation After Treatment of Vulnus Morsum on Domestic Cat Hind Leg: A Case Report - I Nyoman Surya Tri Hartaputera; I Wayan Gorda; I Wayan Wirata (Media Kedokteran Hewan, 2024)
A Vulnus morsum is a term used to describe a wound resulting from an animal bite. Specifically, wounds inflicted by cat bites are referred to as Vulnus morsum felis. A domestic cat named Sinto, approximately one-year-old with a body weight of 2.4 kg was examined with complaints of a torn wound on the right leg after fighting with another cat. The clinical examination results showed that case cat generally had a body condition score of 4/9 with an alert temperament and an attitude that always lowered its tail to protect the wound. Clinical examination also showed a Vulnus morsum on the hind right leg. A complete blood count showed that the cat had leukocytosis, granulocytosis, and thrombocytopenia. From the results of anamnesis, clinical examination, and supporting examinations, the case cat was diagnosed with Vulnus morsum felis with a fausta prognosis. Treatment was carried out by applying three principles of wound care; cleansing, debridement, and wound closure. In addition to surgical procedures, post-surgery antibiotics and anti-inflammatory drugs were given. The wound was treated and cleaned daily using an antiseptic to help the healing process. The wound found in the case cat were healed after surgical procedures and 12 days of treatment.